Higher education, the arts, and transdisciplinarity: A systematic review of the literature. (November 2021) - van Baalen, Wander M; de Groot, Tamara; Noordegraaf-Eelens, Liesbeth
Against an increasingly compartmentalized educational landscape, we have heard urgent calls for new modes of teaching and learning. In this light, educators from a variety of disciplinary backgrounds turned to transdisciplinarity and the arts for a possible response. The educational initiatives being developed and the related literature are situated across a wide range of themes, disciplines, and methodologies. The fragmented nature of the academic discussion inhibits our capacity to think through the implications of mobilizing the concept of transdisciplinarity within the arts and education. This study addresses the lack of an overview by conducting a systematic review of the literature characterized by a triangular interest in higher education, transdisciplinarity, and the arts. The documents under review amount to 458 unique scientific papers. In our results, we present a metaphorical scale – moving from buzzwords to a theoretically delineated usage – to make sense of the use and conceptualization of transdisciplinarity and we introduce three main ways how the arts are part of transdisciplinary educational compositions. In bringing together literature on education, the arts, and transdisciplinarity, we shed light on relevant similarities between thinking and doing that too often operates in isolation. As such, we aim to facilitate opportunities for mutual learning and present an improved vantage point from which to consider how decisions regarding particular conceptualizations and positionalities feed into our artistic and educational practices.